THERMOBAROMETRY OF ORDINARY CHONDRITES - Zinovieva N.G.; Pletchov P.Yu.; Latyshev N.P.; Granovsky L.B. (My University, 2006)
Ordinary chondrites are the most abundant type of meteorites. However, their genetic interpretation, accepted in modern literature and based on independent investigations of the formation of droplike silicate chondrules and the kamacite matrix, is obviously inconsistent with results of their petrographic and experimental studies, indicating the joint formation of the chondrules and chondrite matrix as a result of the development of iron–silicate immiscibility, which defined their compositional relationships according to Prior’s rules.